Ecological adaptation of smallholders to tropical climate change in the highland zone of South Sulawesi, Indonesia - NURBAYA BUSTHANUL; EYMAL B. DEMMALLINO; HAIRUL RACHMAN SULTANI; MUNSI LAMPE; ACHMAD ISMAIL; AMIR YASSI; LUKMAN DARIS; MUH YAMIN SAUDI; ARIFAH ZAINUDDIN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Busthanul N, Demmallino EB, Sultani HR, Lampe M, Ismail A, Yassi A, Daris L, Saudi MY, Zainuddin A. 2023. Ecological adaptation of smallholders to tropical climate change in the highland zone of South Sulawesi, Indonesia. Biodiversitas 24: 5328-5335. Climate change has adversely affected the stability of agricultural production and livelihood systems, threatening the well-being of farmers in Indonesia, particularly small-scale farmers with limited resources. To mitigate the impacts of climate change on agricultural production, innovative approaches are required. Ecological adaptation is one of such approaches which addresses the threat of climate change. However, studies on ecological adaptation in Indonesia have mostly been concentrated on food crops, with limited attention to horticultural commodities in mountainous regions. This study aims to explore how horticulture farmers in the mountainous region of Enrekang District, South Sulawesi, adapt to the effects of tropical climate change. This study employs a post-positivistic approach, to a case study of the impact of climate change on the horticulture farming community in Enrekang District. The study uses a household survey method to gather quantitative data, while focus group discussions and key informant interviews were used to collect qualitative data using semi-structured and unstructured questionnaires. The study's findings revealed diverse ecological adaptation patterns among horticulture farmers, which include adjustments in planting timing, management of pests and diseases, crop rotation, and the use of pumping systems. In addition to these scientifically based strategies, local knowledge also played a crucial role in adaptation processes. Furthermore, to ensure the sustainability of these ecological adaptation strategies, there is a need for the government and scientists to support and empower local communities collectively. This recognition and collaboration are vital for ensuring the resilience and effectiveness of adaptation efforts in mitigating climate change.